Integrated Nutrient Management on Economics and Energy Utilization in Vegetable Pea Production - Dey, Baby; Singh, M. K.; De, Chhabi; Singh, V. K.; De, Nirmal (International Journal of Bio-resource and Stress Management, 2012)
The productivity, input use efficiency, cost-benefit ratio and energy use pattern of vegetable pea (Pisum sativum L.) production were significantly influenced by the use of integrated nutrient management technology (INM). The on-farm experimental data on three most popular varieties of pea (Azad P1, Azad P3 and Arkel) under different sets of nutrient management treatments with conventional flood irrigation and sprinkler irrigation for five years were collected from Indian Institute of Vegetable Research, Varanasi. Nutrient management with optimum dose of NPK along with sulphur (from organic source i.e. pressmud @ 2 t ha-1) and seed treatments with Rhizobium inoculums coupled with sprinkler irrigation on 28 and 49 days after sowing were found to be a promising agro – technique to enhance seed yield (9.7 -13.5 q ha-1), agronomic/ chemical nutrient use efficiency (0.22/170) and economic return (C: B=1:3.2). The peer conventional farmers’ practice comprising of N, P and K application @ 30, 60 and 80 kg ha-1 respectively followed by flood irrigation just before flowering stage was found to produce 6-9 q ha-1 seed yield with nutrient use efficiency of 0.07/92 and cost-benefit ratio 1:1.96. The output – input energy ratio analysis of vegetable pea cultivation was found to range from 5.5 to 7.2 as compared to 4.2 reported for wheat production in Uttar Pradesh, India. This paper suggested that adoption of developed integrated nutrient management module for vegetable pea cultivation could reap higher economic return and save energy as compared to wheat cultivation in transect 4 of the Gangetic Plain region.